The cumulative therapeutic effect of acupuncture in patients with migraine without aura: Evidence from dynamic alterations of intrinsic brain activity and effective connectivity - Chen, Yilei; Kang, Yingjie; Luo, Shilei; Liu, Shanshan; Wang, Bo; Gong, Zhigang; Huang, Yanwen; Wang, Hui; Zhan, Songhua; Tan, Wenli (Frontiers in Neuroscience, 2022)
Abstract We explored the dynamic alterations of brain intrinsic activity and effective connectivity after acupuncture treatment to investigate the underlying neurological mechanism of acupuncture treatment in patients with migraine without aura (MwoA). The fMRI scans were separately obtained at baseline, after the first and after the 12th acupuncture sessions in 40 patients with MwoA. Compared with healthy controls (HCs), patients with MwoA were mostly showed the decreased dynamic amplitude of low-frequency fluctuation (dALFF) variability in the rostral ventromedial medulla (RVM), superior lobe of left cerebellum (Cerebelum_Crus1_L), right precuneus (PCUN.R) and so on. After acupuncture, the decreased dALFF variability of RVM, Cerebelum_Crus1_L, and PCUN.R progressively recovered. There was gradually increased dynamic effective connectivity (DEC) variability in RVM outflow to the right middle frontal gyrus, left insula, right precentral gyrus, and right supramarginal gyrus, and there was enhanced DEC variability from the right fusiform gyrus inflow to RVM. Furthermore, the increased DEC variability was found from Cerebelum_Crus1_L outflow to the left middle occipital gyrus and the left precentral gyrus, from PCUN.R outflow to the right thalamus. These dALFF variabilities were positively correlated with frequency of migraine attack and negatively correlated with disease duration. The dynamic GCA coefficients of these DEC variability were positively correlated with Migraine-Specific Quality of Life Questionnaire scores, and negatively correlated with the frequency of migraine attacks and visual analog scale scores after acupuncture. Our results provided insight into the dynamic alterations of brain activity and effective connectivity in patients with MwoA after acupuncture intervention. Acupuncture might relieve MwoA by increasing the effective connectivity of RVM, Cerebelum_Crus1_L and PCUN.R to make up the decreased dALFF variability in these brain areas.